The Role of Productive Thinking in Affecting Student Learning with Microcomputers in Accounting Education. - Borthick, A. Faye; Clark, Ronald L. (The Accounting Review, 1986)
ABSTRACT: This study Investigates the role of productive thinking in affecting student attitudes toward, and performance with, microcomputer spreadsheet programs in a managerial/ cost accounting course. Productive thinking is defined as thinking based on an understanding of the nature of problems rather than on memorization of facts and rules. In this experiment covering two academic quarters, students initially indicated strong desire to use microcomputers, but their enthusiasm diminished after the classroom experience with their use. Although there was no performance difference across integrative versus non-integrative assignments, performance was positively related to previous computing experience. Students did feel, however, that computers should be used in other accounting courses. Students also reported that they experienced greater learning with integrative course assignments than with repetitive, non-integrative assignments. This finding suggests that a benefit of computer use in teaching accounting may be the opportunity it offers for problem solving based on Understanding rather than on memorization.